2013
DOI: 10.1088/0004-637x/765/2/125
|View full text |Cite
|
Sign up to set email alerts
|

Hyperaccreting Black Hole as Gamma-Ray Burst Central Engine. I. Baryon Loading in Gamma-Ray Burst Jets

Abstract: A hyperaccreting stellar-mass black hole has been proposed as the candidate central engine of gamma-ray bursts (GRBs). The rich observations of GRBs by Fermi and Swift make it possible to constrain the central engine model by comparing the model predications against data. This paper is dedicated to studying the temporal evolution of central engine parameters for both prompt emission and afterglow phases. We consider two jet launching mechanisms, i.e., ν ¯ ν annihilations and the Blandford-Znajek (BZ) processe,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
175
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 142 publications
(176 citation statements)
references
References 76 publications
0
175
1
Order By: Relevance
“…Recently, Lei et al (2013) investigated the baryon loading processes in the jet powered by these two mechanisms, and calculated the initial Lorentz factor and total power of the jets for the two models. With the data obtained in Sect.…”
Section: The Bh Central Engine Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Lei et al (2013) investigated the baryon loading processes in the jet powered by these two mechanisms, and calculated the initial Lorentz factor and total power of the jets for the two models. With the data obtained in Sect.…”
Section: The Bh Central Engine Modelmentioning
confidence: 99%
“…Lü et al (2012) also discovered a somewhat tighter correlation between Γ 0 and the isotropic mean γ-ray luminosity (L γ,iso ). Lei et al (2013) investigated the baryon loading processses in the hyper-accreting black hole central engine models for the two jet launching mechanisms: the non-magnetized νν -annihilation mechanism and the strongly magnetized BZ mechanism. The two models have distinct predictions between Γ 0 and the total jet power.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the lower β parameter produces higher Lorentz factors of the jets. This result provides a quantitative way to estimate the magnitude of magnetic field of the progenitor, basing on the observed profiles of the GRB lightcurve [13]. We note here that, due to the significant acceleration our outflow achieves, it was necessary to consider a gamma barrier and test different values to exclude any implication on the launched jet variability.…”
Section: Variability Of the Pulses In Short Grb Engine Due To The Magmentioning
confidence: 88%
“…Lei et al (2013a) studied the baryon loading in NDAF and BlandfordZnajek jets. It is found that Blandford-Znajek mechanism can produce "clean" jet.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The NDAF has been extensively investigated and usually compared with the magnetic mechanism (e.g., Narayan et al 2001, hereafter NPK01;Kohri & Mineshige 2002;Di Matteo et al 2002, hereafter DPN02;Chen & Beloborodov 2007;Janiuk et al 2004Janiuk et al , 2007Janiuk et al , 2010Gu et al 2006;Liu et al 2007; Lei et al 2008Lei et al , 2009Lei et al , 2013a. It was for a long time considered as an inefficient model for GRBs.…”
Section: Introductionmentioning
confidence: 99%